Effects of partial pressure of oxygen on sintering of a ZrO2-30 mol% Ti powder mixture. Issue 10 (July 2017) - Lin, Kun-Lin; Lin, Chien-Cheng
Abstract: A powder mixture of ZrO2 -30 mol% Ti was sintered at 1500 °C/h under various controlled partial pressures of oxygen (PaO2 ). The microstructure of each sintered sample was characterized using x-ray diffractometry and analytical transmission electron microscopy/energy-dispersive spectroscopy. TiO and highly oxygen-deficient zirconia were found after sintering at PaO2 2.1×10 −4 atm, which implies that the oxidation–reduction reaction is a controlling mechanism when there is a trace of residual oxygen. When the PaO2 was increased to 1.05×10 −1 atm, the dissolution of residual oxygen and nitrogen in the chamber into the titanium led to the formation of TiO(N) with nitrogen in solid solution. It was inferred that the oxygen in TiO(N) was also supplied by zirconia since the zirconia became oxygen-deficient in the sintered composites. After sintering in air (PaO2 2.1×10 −1 atm), TiO2 and TiN were formed along with nearly stoichiometric zirconia, indicating that oxygen and nitrogen in air played a major role in the oxidation and nitridization reaction of titanium. The degree of oxygen deficiency x in ZrO2−x decreased with increasing oxygen partial pressure, which led to an increased volume fraction of the monoclinic phase.